Consolidation and Crisis in the US Banking Sector 1980-2022 - Christopher Mouré (Capital as Power - Toward a New Cosmology of Capitalism, 2024)
Much of the economic analysis of banking crises focuses on the interplay between concentration and stability. A common theory is that concentration is associated with greater stability, whereas competition is associated with instability. In this view, there is a trade-off between, on the one hand, the higher prices and higher profits associated with a banking cartel, and on the other, frequent banking crises and lower prices caused by a fragmented sector. However, this theory is not entirely convincing. Principally, it tends to treat competition and concentration as independent variables, whereas in reality, causality works both ways: banks actively work to transform the structure of the system and transcend apparent constraints – whether through coordinating interest rates, influencing policy, or by transforming the business landscape through corporate amalgamation. In addition, the last two major banking crises in the US occurred in dramatically different conditions of concentration from one other, complicating any obvious empirical connection between concentration and stability. In this paper, I try to move beyond this hypothesis by investigating the relationship between corporate concentration and banking stability through the lens of organized power. Using a combination of quantitative and qualitative analyses, I make two claims. First, since the 1980s, the differential profitability of large banks has been driven by corporate amalgamation. Second, crises tend to be followed by an increase in the pace of amalgamation. As a result, since the 1980s, banking crises have preceded a dramatic redistribution of resources and control to a handful of large banks. While it is not clear that concentration makes a banking crisis less likely, the evidence suggests that crisis makes concentration more likely. Though the research presented here is only tentative and exploratory, it indicates that since the 1980s, large banks have remade the business and regulatory landscape in ways that defy the logic of a simple binary relationship between concentration and stability, and that this needs to be taken into account when analysing the dynamics of banking crises.
Keywords: G; G2; G3; G01; 330; banks; capital as power; concentration; crisis; mergers & acquisitions; United States